Poor applicability of currently available prognostic scoring systems for prediction of outcome in KIT D816V-negative advanced systemic mastocytosis - Naumann, Nicole; Rudelius, Martina; Lübke, Johannes; Christen, Deborah; Bresser, Jakob; Sotlar, Karl; Metzgeroth, Georgia; Fabarius, Alice; Hofmann, Wolf-Karsten; Panse, Jens Peter; Horny, Hans-Peter; Cross, Nicholas C. P.; et al. (Cancers, 2024)
Within our nationwide registry, we identified a KIT D816V mutation (KIT D816Vpos.) in 280/299 (94%) patients with advanced systemic mastocytosis (AdvSM). Age, cytopenias and the presence of additional somatic mutations confer inferior overall survival (OS). However, little is known about the characteristics of KIT D816V-negative (D816Vneg.) AdvSM. In 19 D816Vneg. patients, a combination of clinical, morphological and genetic features revealed three subgroups: (a) KIT D816H- or Y-positive SM (KIT D816H/Ypos., n = 7), predominantly presenting as mast cell leukemia (MCL; 6/7 patients), (b) MCL with negative KIT sequencing (KITneg. MCL, n = 7) and (c) KITneg. SM with associated hematologic neoplasm (KITneg. SM-AHN, n = 5). Although >70% of patients in the two MCL cohorts (KIT D816H/Ypos. and KITneg.) were classified as low/intermediate risk according to prognostic scoring systems (PSS), treatment response was poor and median OS was shorter than in a KIT D816Vpos. MCL control cohort (n = 29; 1.7 vs. 0.9 vs. 2.6 years; p < 0.04). The KITneg. SM-AHN phenotype was dominated by the heterogeneous AHN (low mast cell burden, presence of additional mutations) with a better median OS of 4.5 years. We conclude that (i) in MCL, negativity for D816V is a relevant prognostic factor and (ii) PSS fail to correctly classify D816Vneg. patients.